Lung Abnormalities in Systemic Sclerosis Patients through Spirometry, Chest X-Ray, and High-Resolution Computed Tomography Scan - Sumartini Dewi; Waliyyuddin Robbani; Iceu Dimas Kulsum (Faculty of Medicine Universitas Padjadjaran, 2022)
Background: Systemic sclerosis (SSc) is a multisystem autoimmune illness with a wide range of clinical symptoms. The pulmonary organ manifestations frequently occur, but the symptoms are non-specific. Radiological examination and pulmonary function tests (spirometry) are needed to detect lung abnormalities in SSc patients. This study aimed to obtain information about the overview of lung abnormalities in SSc patients through spirometry, chest x-ray, and high-resolution computed tomography (HRCT) scan examination.Methods: A descriptive qualitative study was conducted on 75 SSc patients registered in Dr. Hasan Sadikin General Hospital Bandung from January 2019 to December 2020. Data were collected with a total sampling method and presented in proportions and percentages.Results: The majority of subjects were affected by cutaneous 73 (97%), pulmonary 29 (39%), and musculoskeletal 17 (23%) involvement. Spirometry revealed that 43 subjects (57%) had restrictive lung disease, with one false-positive case and two false-negative cases. On a chest x-ray, 45 (60%) of subjects had abnormalities. The majority of subjects were found to have Ground-glass opacities on HRCT scans. Ground-glass opacities were discovered in 46 subjects (82%) and 27 subjects (60%) were identified as having severe fibrosis scores.Conclusion: According to spirometry results and abnormalities on chest x-ray and HRCT scans, the majority of SSc patients have restrictive lung disease.